Snackfruit Village Festival: A Study of the Revitalization of Local Cultural Values from an Ethno-Social Perspective - Novia Hardiyanti (FKIP, Universitas Palangka Raya, 2025)
Local cultural wisdom in each region is unique and different; this is why it is important to maintain it. It indicates the unique characteristics of an area, including its social field. The distinctive social culture in each region generally adheres to positive teachings and is worth preserving. This research aims to explore how the snakefruit village festival functions as a tool to maintain and celebrate cultural identity and local wisdom. This research is qualitative research with an ethno-social based phenomenological approach. Data collection is done through observation, in-depth interviews, and documentation studies, as well as through local figures and residents. Data triangulation is carried out through source triangulation. The research results show that (1) internalizing character values ​​is carried out through five stages: value acceptance, response, selection, internalization, and actualization. On the other hand, the character values ​​that emerge as a form of internalization of the local wisdom of the Snakefruit Village festival include religious values, cooperation, tolerance, and caring for the environment. (2) the community has three forms of social capital, Bonding, Bridging, and Linking, which are forms of community cooperation through various parties for the event’s success. The implication of the results of this research is the need for continuous support in developing and promoting the Snakefruit Festival as a manifestation of cultural values ​​in Rengel Village through collaborative efforts between the government, cultural actors, and the community. In this case, the Snakefruit Festival can effectively strengthen and expand understanding and appreciation of Javanese cultural identity in Rengel Village, Tuban Regency